Austerity and Public Administration: Italy Between Modernization and Spending Cuts. (November 2014) - Di Mascio, Fabrizio; Natalini, Alessandro
This article analyzes the Italian government's response to the sovereign debt crisis. Given the severity of the fiscal crisis affecting Italy, this article provides insights about the crisis's implication for public administration in such a politically sensitive environment where drastic and far-reaching measures had to be taken by the government. Drawing on the historical institutionalist approach, the impact of the crisis is not considered in isolation but in the context of the historical trajectory that has shaped the government's capacity to respond. To assess the crisis's implications for public administration, the empirical analysis focuses on public employment as an area that is especially exposed to fiscal restraint. The findings reveal that the current crisis has been managed with straight cutback management, as public administration has been considered by policy makers just as a source of public expenditure to be squeezed rather than as a provider of public services in need of modernization so as to sustain economic growth.